The improvement of English speaking skill of Buddhist monks and novices in tourist attractive temples, in Meuang district, Chiang Mai province - ขันสำโรง สำราญ; เลาลี ทิพย์พนากรณ์; ชัยสิทธิ์ วิสุทธิไชย (Community and Social Development Journal, 2018)
The purpose of the research was to provide English training manual in order to develop English speaking skill about Buddhism, local art and culture of the monks and novices and to study the opinions of the foreigners who listen to the explanation of the monks and novices about Buddhism, local art and culture at tourist attractive temples. The research samples consisted of 40 monks and novices at popular temples in Muang district, Chiagmai province and 36 foreign tourists visiting the model Buddhist popular temples; Wat Phrasingha, Wat Suandok and Wat Chiangman. The research instruments comprised a set of training manual, evaluation form, interview form and questionnaire. Research findings showed that the training manual was effectively helped the monks and novices improve their speaking skill at (E1/E2) 69.79/81.42. It was also shown that the average scores of the samples after participating in the training and practice the first time (=69.79±12.92) and the second time (=81.42±9.62) were higher than before being trained and practice according to the training manual at (=52.12±12.92) which were at the .001 level of statistical significance. From the interview, the tourists were happy and satisfied with the explanation of the monks and novices. They got more and useful information about Buddhism, art and culture. They also viewed that the activity should be continued.